Endothelial Phenotype Evoked by Low Dose Carvedilol in Pulmonary Hypertension - Cheong, Hoi I; Farha, Samar; Park, Margaret M.; Thomas, James D.; Saygin, Didem; Comhair, Suzy A. A.; Sharp, Jacqueline; Highland, Kristin B.; Tang, W. H. Wilson; Erzurum, Serpil C. (Frontiers in Cardiovascular Medicine, 2018)
Background: The therapeutic benefits of β-blockers are well established in left heart failure. The Pulmonary Arterial Hypertension Treatment with Carvedilol for Heart Failure [PAHTCH] study showed safety and possible benefit of carvedilol in pulmonary arterial hypertension (PAH) associated right heart failure over 6 months. This study aims at evaluating the short-term cardiovascular effects and early mechanistic biomarkers of carvedilol therapy. Methods: Thirty patients with pulmonary hypertension (PH) received low dose carvedilol (3.125 mg twice daily) for 1 week prior to randomization to placebo, low-dose or dose-escalating carvedilol therapy. Echocardiography was performed at baseline and 1 week. Exercise capacity was assessed by 6-minute walk distance (6MWD). The L-arginine/ nitric oxide pathway and other biological markers of endothelial function were measured. Results: All participants tolerated one week of carvedilol without adverse effects. After 1 week of carvedilol, 6MWD and heart rate at peak exercise did not vary (both p > 0.1). Heart rate at rest and 1-minute post walk dropped significantly (both p < 0.05) with a trend for increase in heart rate recovery (p = 0.08). Right ventricular systolic pressure (RVSP) decreased by an average of 13mmHg (p = 0.002). Patients who had a decrease in RVSP of more than 10mm Hg were defined as responders (n = 17), and those with a lesser drop as non-responders (n = 13). Responders had a significant drop in pulmonary vascular resistance (PVR) after one week of carvedilol (p = 0.004). In addition, responders had a greater decrease in heart rate at rest and 1-minute post walk compared to non-responders (both p < 0.05). Responders had higher plasma arginine and global bioavailability of arginine at baseline compared to non-responders (p = 0.03 and p = 0.05 respectively). After one week of carvedilol, responders had greater increase in urinary nitrate (p = 0.04). Responders treated with carvedilol had a sustained drop in RVSP and PVR after 6 months of carvedilol with no change in cardiac output. Conclusions: Low-dose carvedilol for one week can potentially identify a PH responder phenotype that may benefit from β-blockers that is associated with less endothelial dysfunction.